2011
DOI: 10.3109/13651501.2011.617458
|View full text |Cite
|
Sign up to set email alerts
|

Relations between childhood traumatic experiences, dissociation, and cognitive models in obsessive compulsive disorder

Abstract: These results suggest that in spite of pathological connotation of dissociative experiences, dissociation may primarily constitute a cognitive trait which is strongly associated with cognitive processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 35 publications
2
24
0
5
Order By: Relevance
“…For example, a recent population based study in Ireland, reported rates of contact sexual abuse in 20% of girls and 16% of boys (McGhee, Garavan, Byrne, O'Higgins, & Conroy, 2011). In addition to child sexual abuse (CSA) and physical abuse (King et al, 2011;Selvi et al, 2012;Zlotnick et al, 2008), emotional abuse, physical abuse, emotional neglect and the number of types of childhood trauma suffered have also been associated with an increased likelihood of individuals subsequently suffering mental health disorders and having a reduced health-related quality of life in adulthood (Benjet, Borges, Méndez, Fleiz, & Medina-Mora, 2011;Draper et al, 2008;Huang, Schwandt, Ramchandani, George, & Heilig, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent population based study in Ireland, reported rates of contact sexual abuse in 20% of girls and 16% of boys (McGhee, Garavan, Byrne, O'Higgins, & Conroy, 2011). In addition to child sexual abuse (CSA) and physical abuse (King et al, 2011;Selvi et al, 2012;Zlotnick et al, 2008), emotional abuse, physical abuse, emotional neglect and the number of types of childhood trauma suffered have also been associated with an increased likelihood of individuals subsequently suffering mental health disorders and having a reduced health-related quality of life in adulthood (Benjet, Borges, Méndez, Fleiz, & Medina-Mora, 2011;Draper et al, 2008;Huang, Schwandt, Ramchandani, George, & Heilig, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the relationship between ACE and OCD is scarce and inconclusive (Selvi et al, 2012). Some studies report no association between ACE and OCD and few others support higher ACE in those with OCD, but possibly mediated by coexisting affective, anxiety, substance use and eating disorders (Visser et al, 2014;Briggs and Price, 2009;Benedetti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Muitos estudos têm apontado para a relação existente entre os diversos tipos de negligência e de abuso sofridos na infância e o aumento da probabilidade de apresentar transtornos mentais no futuro (BENJET et al, 2011;SELVI et al, 2012;ZLOTNICK et al, 2008). Estudo realizado na Irlanda investigou a vivência de traumas na infância entre 129 indivíduos adultos, pacientes de serviços de saúde mental.…”
Section: Introductionunclassified